Influence of Process Variables on The Density of Aluminium Chip-Base Feedstock Prepared for Non-Melted Hot Extrusion Recycling - Wagiman, Abdullah; Mustapa, Mohammad Sukri; Lajis, Mohd Amri; Shamsudin, Shazarel; Mohamad, Mahmod Abd Hakim; Rady, Mohammed Hussien (semarak ilmu, 2024)
Non-melted recycling of aluminum chips through hot extrusion offers a sustainable manufacturing alternative. However, achieving void-free extrudates is crucial, as air trapped in chip-based feedstocks may cause microvoids. In this work, heat treatment was performed on the chips before they were compacted into the feedstock. The effects of annealing temperature, time, and compaction pressure on density were investigated. The experiment was conducted using a 23 factorial design, and an ANOVA was used to identify the main parameters. Visual inspections and testing were conducted on the compacted feedstocks. The results indicate that parameters such as compaction pressure, annealing temperature, and annealing time arem statistically significant. The main parameter is the compaction pressure, followed by the annealing temperature, the interaction between the annealing temperature and the annealing time, and finally the annealing time. At high annealing temperatures, annealing time does not significantly affect density, but at low temperatures, annealing time plays a crucial role. Non-annealed chip feedstocks exhibit lower relative density compared to annealed ones. A higher feedstock density leads to a reduction in surface voids on the final product. This work highlights the importance of heat treatment and compaction pressure in achieving quality extrudates, thus advancing the non-melted recycling technique for sustainable manufacturing.